2007
DOI: 10.1093/humrep/del499
|View full text |Cite
|
Sign up to set email alerts
|

A frequent Y chromosome b2/b3 subdeletion shows strong association with male infertility in Han-Chinese population

Abstract: Our data showed a higher frequency of deletion events in this Han-Chinese population than in populations elsewhere in the world. The classical AZF deletions were the primary genetic factors for spermatogenic failure, while no significant association was found for AZFc subdeletions with sperm concentration. However, the b2/b3 subdeletion was significantly associated with idiopathic male infertility (odds ratio, 2.93; 95% confidence interval 1.34-6.39) (P = 0.005), indicating a potential impairment of male ferti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
6
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 27 publications
8
73
6
1
Order By: Relevance
“…Similar observations were made with respect to b2/b3 subdeletions in the Han-Chinese population, in which the frequency was significantly high. 36 However, other studies have reported very low frequencies of these subdeletions and found no association with infertility and/or spermatogenesis. 14,16,19,27,34,37 Either genetic background of the population studied or the type of infertility might explain the reasons in the frequencies of the different subdeletions.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Similar observations were made with respect to b2/b3 subdeletions in the Han-Chinese population, in which the frequency was significantly high. 36 However, other studies have reported very low frequencies of these subdeletions and found no association with infertility and/or spermatogenesis. 14,16,19,27,34,37 Either genetic background of the population studied or the type of infertility might explain the reasons in the frequencies of the different subdeletions.…”
Section: Discussionmentioning
confidence: 93%
“…This is in line with studies from European and Han-Chinese populations. 10,17,36 The overall difference in the frequencies of subdeletions between Indian and Chinese populations could be because of the genetic background of the study participants. The prevalence of subdeletions such as b1/b3 and b2/b3 only in the infertile group has reinforced our view that these subdeletions might have some impact on spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, new types of AZFc deletions, called "partial deletions," have been reported , which remove approximately half of the AZFc gene content-including two DAZ, one CDY1 copies and one BPY2 copy-and arise by the same molecular mechanism of the complete AZF microdeletions. Among them, gr/gr partial deletion is considered a genetic risk factor for spermatogenic impairment by a number of research groups, including ours (see Table 1), while b2/b3 and b1/b3 deletions seem not to have signiWcant eVects on male fertility (Giachini et al 2005;Hucklenbroich et al 2005;Lynch et al 2005;Repping et al 2004) with the exception of one study in the Han-Chinese population (Wu et al 2007).…”
Section: Introductionmentioning
confidence: 79%
“…With the exception of one study among Han-Chinese population (Wu et al, 2007), all other studies reported no association between the b2/b3 deletion and impaired spermatogenesis. The results of the gr/gr deletion are more inconsistent; it is considered a new genetic risk factor by a number of research groups de Llanos et al, 2005;Ferlin et al, 2005;Gianchini et al, 2005, Gianchini et al, 2008, but not by the others (Machev et al, 2004;Hucklenbroich et al, 2005;Ravel et al, 2006;Carvalho et al, 2006;Lardone et al, 2007a;Lin et al, 2007).…”
Section: Partial Azfc Deletionsmentioning
confidence: 85%